Efektivitas Pendekatan Pembelajaran Matematika Realistik terhadap Kemampuan Literasi Matematis Siswa SMP Ditinjau dari Gaya Belajar - Nely Murni; Mulhamah; Sucipto, Lalu (Jurnal Derivat: Jurnal Matematika dan Pendidikan Matematika, 2025)
This study aims to examine the effect of the Realistic Mathematics Education (RME) approach on students’ mathematical literacy skills and to determine whether learning styles contribute to variations in learning outcomes. This research employs a quantitative approach with a quasi-experimental method using a Nonequivalent Pretest–Posttest Control Group Design involving two eighth-grade classes. Data were collected through mathematical literacy tests administered as pretests and posttests, a learning-style questionnaire, and an observation sheet to evaluate the implementation of the learning approach. The data were analyzed using an independent t-test and Two-Way ANOVA. The results show that students taught using the RME approach achieved higher posttest scores, with the experimental class obtaining an average of 69.46 (SD = 6.432), compared to the control class with an average of 58.21 (SD = 8.189). The independent t-test indicated a significant difference between the two groups (t = –5.717; p = 0.000), suggesting that the RME approach is effective in improving students’ mathematical literacy skills. Furthermore, visual, auditory, and kinesthetic learning styles were found to have no significant effect on mathematical literacy, and no interaction was observed between the learning approach and learning styles. These findings indicate that the improvement in mathematical literacy is primarily influenced by the instructional approach rather than differences in students’ learning styles.